Cytotoxic and pro-apoptotic effects of botanical drugs derived from the indigenous cultivated medicinal plant Paris polyphylla var. yunnanensis - Yan, Xiu-Xiang; Zhao, Yan-Qiang; He, Yun; Disayathanoowat, Terd; Pandith, Hataichanok; Inta, Angkhana; Yang, Li-Xin (Frontiers in Pharmacology, 2023)
Cancer is one of the top two leading causes of death worldwide. Ethnobotanical research, it is one of methods, which is able to discover effective anticancer drugs based on “prototype” of indigenous people’s historical experiences and practices. The rhizomes of Paris polyphylla var. yunnanensis (Franch.) Hand.-Mazz. have been used as botanical drugs to treat cancer by Yi, Bai, Dai, and Naxi ethnic groups in Yunnan, China, where this species is widely cultivated in a large scale in Yunnan. To identify the substances of anticancer activities based on indigenous medicine knowledge, chromatography was performed to separate saponins from the rhizomes of P. polyphylla var. yunnanensis, followed by spectroscopy to determine the structure of six isolated saponins. In this study, five extracts and six pure saponins showed significant inhibitory cytotoxic activities of three human liver cancer cell lines (SMMC-7721, HepG2, and SK-HEP-1) and one non-small-cell lung cancer cell line (A549). The contents of Paris saponins I, II, and VII were 6.96% in the rhizomes of P. polyphylla var. yunnanensis, much higher than Chinese Pharmacopoeia standards (0.6%). Six saponins induced significant apoptosis and cell cycle arrest in three human cancer cell lines (A549, SMMC-7721, and HepG2), which was associated with the loss of mitochondrial membrane potential. The result of this study support that cultivated P. polyphylla var. yunnanensis could be a substitute for wild resource as an anticancer medicine based on indigenous medicine knowledge.